Between Monologue and Dialogue in Social Life – the Philosophies of Martin Buber and Józef Tischner - Mizdrak, Inga (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2019)
Monologue and dialogue are contextual categories. They can be analysed from many different viewpoints, revealing their multiple meanings and their axiological-anthropological-social character. Both communication structures can refer to important social and individual problems.The article examines the meaning and importance of monologue and dialogue in social life. Martin Buber and Józef Tischner explain the real meaning of true (honest) dialogue, by pitting it against the monological way of living. They see dialogue as residing on the plane of life itself (Buber) and affecting the space “between” I and You (Buber, Tischner). Monologue seems to be not only the opposite of dialogue but also to be an incomplete structure that requires complementation. Buber and Tischner present dialogue as an essential human experience. The individual is described as an entity “invited to a conversation” (turned to the other and towards the other). Through this, they crystallise the essence of dialogue, in which freedom and responsibility play the key roles. Facing each other, the subjects must free themselves from prejudice and remove the armor of pretense. The answer to a question coming from another human being creates a dialogical bond of participation in values. Dialogue transcends the monological “being for oneself” of the subject, towards “being for others”. As a result, social reality gains a new meaning, becoming the space for reciprocity, solidarity and social life.